A Co9S8 microsphere and N-doped carbon nanotube composite host material for lithium-sulfur batteries - Xi, Yakun; Angulakshmi, Natarajan; Zhang, Bingyin; Tian, Xiaohui; Tang, Zhihao; Xie, Pengfei; Chen, George Z.; Zhou, Yingke (2020)
Lithium-sulfur batteries have emerged as extraordinarily favorable energy storage devices due to their high specific capacity and energy density, safety and low cost. Unfortunately, the wide applications of lithium-sulfur batteries are hampered by several issues, such as the low electronic conductivity and slow redox kinetics, serious volumetric expansion and polysulfide “shuttle effect”. To overcome these issues, in our work, we design and synthesize a composite sulfur host material of Co9S8 microspheres and N-doped carbon nanotubes, where the metallic sulfide Co9S8 with a good conductivity enables the immobilization of the polar lithium polysulfides owing to the strong polar chemisorptive capability, and the one dimensional N-doped carbon nanotubes can provide channels for fast electron and lithium-ion transport. As the lithium polysulfides are well confined, and the redox conversions are promoted, the Co9S8@N-CNTs/S-based lithium-sulfur battery possesses a superior energy storage performance, exhibiting a large specific capacity of 1233 mAh g-1 at 0.1 C and an outstanding cyclic performance, with a low decay of 0.045% per cycle and a Coulombic efficiency of more than 99% after 1000 cycles.